2021
DOI: 10.1038/s42003-021-01971-z
|View full text |Cite
|
Sign up to set email alerts
|

Graphomotor memory in Exner’s area enhances word learning in the blind

Abstract: Handwriting is thought to impede vocabulary learning in sighted adults because the motor execution of writing interferes with efficient audiovisual processing during encoding. However, the motor memory of writing may facilitate adult word learning when visual sensory inputs are severely restricted. Using functional MRI, we show that late-blind participants, but not sighted participants, learned novel words by recruiting the left dorsal premotor cortex known as Exner’s writing area and its functional coupling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…The small number of patients in the original description, in tandem with the absence of pure agraphia symptoms plus the interindividual variability in the lesion anatomy, is partially why Exner’s hypothesis is still debated (Roux et al 2010 ). There are isolated reports of Exner’s area involved in reading and writing (Roux et al 2009 ) and word learning in the blind (Mizuochi-Endo et al 2021 ). In our study, Exner’s area has been identified as a contributing cortical region in the fMRI analysis, its disconnection from the inferior frontal gyrus and the precentral gyrus has been shown as a critical white matter connection in the disconnectome analysis, and the typical lesion that would explain most the variance in reading has also been identified in the triangle between the IFG/MFG and preC gyrus (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The small number of patients in the original description, in tandem with the absence of pure agraphia symptoms plus the interindividual variability in the lesion anatomy, is partially why Exner’s hypothesis is still debated (Roux et al 2010 ). There are isolated reports of Exner’s area involved in reading and writing (Roux et al 2009 ) and word learning in the blind (Mizuochi-Endo et al 2021 ). In our study, Exner’s area has been identified as a contributing cortical region in the fMRI analysis, its disconnection from the inferior frontal gyrus and the precentral gyrus has been shown as a critical white matter connection in the disconnectome analysis, and the typical lesion that would explain most the variance in reading has also been identified in the triangle between the IFG/MFG and preC gyrus (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The small number of patients in the original description in tandem with the absence of pure agraphia symptoms plus the interindividual variability in the lesion anatomy is partially the reasons why Exner’s hypothesis is still debated (Roux et al, 2010). There are isolated reports of Exner’s area being involved in reading and writing (Roux et al, 2009), as well as word learning in the blind (Mizuochi-Endo et al, 2021). In our study, Exner’s area has been identified as a contributing cortical region in the fMRI analysis, its disconnection from the inferior frontal gyrus and the precentral gyrus has been shown as a critical white matter connection in the disconnectome analysis, and the typical lesion that would explain most the variance in reading has also been identified in the triangle between the IFG/MFG and preC (Figure 3a-c).…”
Section: Discussionmentioning
confidence: 99%
“…When learning a decoding system, hand writing is decoded using the language system. In this hand writing process, the visual and auditory systems resonate along with physical or motor embodiment processes to associate phoneme-word correspondences (Guan et al, 2011(Guan et al, , 2015Mizuochi-Endo et al, 2021).…”
Section: Hand Writing Facilitates Sound-form Meaning Integrated Learningmentioning
confidence: 99%